2007
DOI: 10.1007/s00402-007-0499-0
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral osteochondritis dissecans of the lateral femoral condyle following bilateral total removal of lateral discoid meniscus: a case report

Abstract: Osteochondritis dissecans (OCD) of the lateral femoral condyle sometimes occurs with a discoid lateral meniscus. Recently, it was reported that OCD of the lateral femoral condyle occurred after total removal of the lateral meniscus. We report the case of a 12-year-old boy with bilateral OCD of the lateral femoral condyle following bilateral total removal for discoid lateral meniscus. Valgus deviation of the knee after total removal and increased sporting activity might have concentrated excessive stress on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 10 publications
0
17
0
1
Order By: Relevance
“…Bilateral knee involvement has been reported to exist in 13% to 30% of juvenile patients with OCD lesions, but outcome data and even lesion characteristics are lacking in these studies. [2][3][4]8,11,[21][22][23][24][25][26][27][28] The large, multicenter review of the Micro fx = 2/5 healed *Healing rates between osteochondritis dissecans lesions located on the medial femoral condyle were significantly better than lesions on the lateral femoral condyle (P < 0.0001). European Pediatric Orthopedic Society by Hefti et al 8 reported bilateral involvement in 13% of patients, but failed to mention specific lesion location in this subset of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral knee involvement has been reported to exist in 13% to 30% of juvenile patients with OCD lesions, but outcome data and even lesion characteristics are lacking in these studies. [2][3][4]8,11,[21][22][23][24][25][26][27][28] The large, multicenter review of the Micro fx = 2/5 healed *Healing rates between osteochondritis dissecans lesions located on the medial femoral condyle were significantly better than lesions on the lateral femoral condyle (P < 0.0001). European Pediatric Orthopedic Society by Hefti et al 8 reported bilateral involvement in 13% of patients, but failed to mention specific lesion location in this subset of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated impaction in the immature chondral structure after resection of the discoid meniscus might predispose to the development of OCD in the lateral femoral condyle53,54). In addition, the change of alignment to valgus after resection of a thick discoid meniscus can lead to concentrated stress on the lateral femoral condyle55).…”
Section: Treatmentmentioning
confidence: 99%
“…There are also several case reports suggesting a relationship between the development of OCD. 14,15 The first was a case of a 12-year old who developed bilateral OCD of the lateral femoral condyle (LFC) several years after total removal of symptomatic bilateral discoid menisci. 15 The second case report, also a 12-year old, reported the presence of a large OCD of the LFC in the presence of an incomplete lateral discoid meniscus.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 The first was a case of a 12-year old who developed bilateral OCD of the lateral femoral condyle (LFC) several years after total removal of symptomatic bilateral discoid menisci. 15 The second case report, also a 12-year old, reported the presence of a large OCD of the LFC in the presence of an incomplete lateral discoid meniscus. 14 Each of the preceding studies strengthens the argument of an associated between the development of OCD and the discoid menisci, however they all are in skeletally immature patients.…”
Section: Discussionmentioning
confidence: 99%